Graduate Enrollment and Degrees 1986 to 1991 - Syverson, Peter D.; Welch, Stephen R.; Council of Graduate Schools, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1993)
This report presents a summary of the findings of the first 6 years of a survey of graduate enrollment in 588 institutions in the United States. The enrollment survey was mailed each year to the approximately 630 institutions who are members of the Council of Graduate Schools or one of the four regional graduate associations. The tables and accompanying analyses are divided into two chapters. Chapter 1 highlights the results of the fall 1991 survey, including a profile of graduate enrollment for each of the four regional associations. The second chapter describes trends in graduate enrollment and degrees over the 1986 to 1991 period. Analysis indicates that graduate enrollment has increased an average of 2 percent per year between 1986 and 1991, that numbers of women increased slightly faster than numbers of men, and that health sciences, public administration, and the humanities and arts exhibited the greatest average enrollment growth. A feature of the report is the subdividing of doctoral institutions into two categories, Research I (Carnegie Classification system) and Doctorate-Granting (all other institutions granting the doctorate). The 1991 taxonomy now includes the biological sciences and health sciences as separate fields. Appendixes contain a copy of the survey questionnaire, a taxonomy display, and methodological information. (JB)
Availability: Council of Graduate Schools, One Dupont Circle, N.W., Suite 430, Washington, DC 20036 (free).
Administrators.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Citizenship; Degrees (Academic); Enrollment; Enrollment Trends; Ethnicity; Graduate Students; Graduate Study; Higher Education; School Surveys; Sex Differences; Student Characteristics; Reports, Research